A facile and green template-engaged synthesis of PbSe nanotubes with the assistance of Vc. Issue 37 (3rd September 2018) - Fan, Huaiyun; Gao, Shiyong; Xu, Zhikun; Jiao, Shujie; Yu, Qi; Zhang, Yong; Wang, Jinzhong; Zhang, Xitian; Zhao, Liancheng
Abstract : PbSe nanotubes (NTs) were synthesized through a low cost, facile and green hydrothermal route in combination with the assistance of ascorbic acid. Abstract : PbSe nanotubes (NTs) were synthesized through a low cost, facile and green hydrothermal route in combination with the assistance of ascorbic acid. In the hydrothermal reaction process, Se nanowires were not only used as templates, but also as a Se ion source to provide Se precursors for the growth of PbSe NTs. The prepared tubular crystals with a cubic structure have a length of 1–6 μm and an average diameter of ∼120 nm. Experimental results show that the amount of ascorbic acid and Pb 2+ concentration play important roles in the formation of PbSe NTs, and a possible growth mechanism of PbSe NTs has also been presented. Additionally, the photocatalytic activity of the PbSe NTs was investigated and the results establish that PbSe NTs, in the presence of H2 O2, showed a high photodegradation efficiency for methylene blue (MB). A probable photocatalytic mechanism for PbSe NTs is also discussed.